A New Generalization of the Haddock Conjecture. Issue 5 (3rd September 2017) - Xiao, Songlin
Abstract: In this paper, we establish some new criteria on the boundedness and asymptotic constancy of solutions for a class of scalar neutral functional differential equations with time-varying delays via differential inequality techniques. Our results are an improvement of existing ones and generalization of the Haddock conjecture.